Linear PVA–DTPA–Gd conjugate for magnetic resonance imaging. Issue 63 (12th November 2019) - Xu, Weibing; Lin, Zhiyan; Li, Guichen; Long, Haitao; Du, Mingyuan; Fu, Guorui; Pu, Lumei
Abstract : In this study, we report the preparation and characterization of the PVA–DTPA–Gd conjugate as a potential MRI contrast agent (CA). Abstract : In this study, we report the preparation and characterization of the PVA–DTPA–Gd conjugate as a potential MRI contrast agent (CA). The r 1 value and the r 2 / r 1 ratio were about 5.6 mM −1 s −1 and 1.31, respectively. In vitro toxicity studies not only demonstrated that the polymeric system possessed good biocompatibility, but also proved that the conjugate could be an attractive candidate for CA.